Association of Chronic Psoriasis with Syndrome X: Psoriasis and Metabolic Syndrome - Bacha, Muhammad Faisal; Erfan, Muhammad; Noaman, Muhammad; Sayed, Tahir Mukhtar; Maqsood, Jehanzaib; Baig, Wajahat Sultan (Pakistan Journal of Health Sciences, 2025)
Psoriasis is a chronic skin disorder and has been associated with a number of chronic inflammatory conditions. Syndrome X, which is commonly seen in our population and is responsible for major cardiovascular events, has been found to be linked with chronic skin disorders. Objective: To find out the link between Syndrome X and chronic plaque psoriasis in our population, to estimate the disease burden and plan the management strategies accordingly. Methods: This study included 130 participants selected through consecutive sampling including 65 patients as diagnosed cases of chronic plaque psoriasis and rest of 65 were controls. Data collection involved measuring body size, blood pressure, and lab investigations with lipids panel, complete blood counts and fasting sugar levels. For the diagnosis of Syndrome X, National Cholesterol Education Program Adult Treatment Panel III (NCEP ATP III) criteria was applied. Results: The study results revealed that Syndrome X was common in the psoriasis patients (41.5%) than the other group (23.1%) with a p value of 0.035. The majority of psoriasis patients were obese, had hypertension, sugar levels were elevated, higher triglycerides, and low HDL cholesterol. The bivariate analysis indicated that psoriasis was associated with the high tendency of developing syndrome X (p value of 0.021). Conclusion: The study findings highlighted that appropriate treatment of syndrome X in patients with chronic psoriasis can reduce the cardiovascular complications.